2014
DOI: 10.3892/or.2014.3258
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of oral squamous cell carcinoma cells to cetuximab is associated with EGFR insensitivity and enhanced stem cell-like potency

Abstract: Abstract. Cetuximab, a specific anti-epidermal growth factor receptor (EGFR) monoclonal antibody, is used in cancer treatment. Although development of resistance to cetuximab is well recognized, the underlying mechanisms remain unclear.In the present study, we characterized cetuximab-resistant oral squamous cell carcinoma (OSCC) cell lines. The human OSCC cell lines HSC3, HSC4 and SAS were used in the present study. Effects of inhibitors including cetuximab on growth in cells were assessed by MTT assays. South… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
2
20
0
1
Order By: Relevance
“…The proliferation of SAS cells, which possess a stem cell-like potency (52), was resistant to cetuximab in monolayer culture conditions, despite the phosphorylation of EGFR; however, the growth of SAS cell aggregates, in which EGFR levels were increased, was sensitive to cetuximab (30). In the present study, it was demonstrated that SAS cell migration is also sensitive to the EGFR inhibitors cetuximab and AG1478.…”
Section: Discussionmentioning
confidence: 56%
“…The proliferation of SAS cells, which possess a stem cell-like potency (52), was resistant to cetuximab in monolayer culture conditions, despite the phosphorylation of EGFR; however, the growth of SAS cell aggregates, in which EGFR levels were increased, was sensitive to cetuximab (30). In the present study, it was demonstrated that SAS cell migration is also sensitive to the EGFR inhibitors cetuximab and AG1478.…”
Section: Discussionmentioning
confidence: 56%
“…Furthermore, EGFR phosphorylation levels were increased by serum stimulation (Fig. 1B), although SAS cells actively proliferate in serum-free culture conditions as described previously (19). These results indicate that the inhibitory effects of cetuximab on EGFR phosphorylation are weaker than those of AG1478, and EGFR phosphorylation signals are not the main factor inducing proliferation of SAS cells in monolayer cultures.…”
Section: Cetuximab Inhibits Egfr Phosphorylation Resulting In Reducementioning
confidence: 47%
“…We previously reported that SAS cell growth is poorly sensitive to cetuximab or AG1478 treatment in a monolayer culture, even though EGFR is expressed and phosphorylated (19), indicating that EGFR phosphorylation is minimally involved in SAS cell proliferation.…”
Section: Cetuximab Inhibits Egfr Phosphorylation Resulting In Reducementioning
confidence: 99%
See 1 more Smart Citation
“…EGFR-targeted therapies, including gefitinib (Iressa ® ; AstraZeneca, London, UK) (26,(28)(29)(30) and cetuximab (Erbitux ® ; Eli Lilly and Company, Indianapolis, IN, USA) (31,32), have been studied extensively as potential methods of blocking the cancer-promoting functions of EGFR in OSCC. However, although it has been reported that EGFR inhibitors are initially beneficial for the treatment of cancer, resistance to the inhibitors eventually develops (21,33). Therefore, an alternative strategy was investigated in the present study, in which rather than targeting the EGFR protein, the expression of its gene, EGFR, in OSCC was downregulated using RNAi techniques.…”
Section: Discussionmentioning
confidence: 99%